Rhetoric before and beyond the Greeks - Lipson, Carol; Binkley, Roberta A., 1941- (State University of New York, 2004)
"Focusing on ancient rhetoric outside of the dominant Western tradition, this collection examines rhetorical practices in Egypt, Mesopotamia, Israel, and China. The book uncovers alternate ways of understanding human behavior and explores how these rhetorical practices both reflected and influenced their cultures. The essays address issues of historiography and raise questions about the application of Western rhetorical concepts to these very different ancient cultures. A chapter on suggestions for teaching each of these ancient rhetorics is included."--Jacket